PENGARUH PERMAINAN TRADISIONAL LOMPAT TALI TERHADAP HASIL BELAJAR LOMPAT TINGGI DI SMPN 16 PONTIANAK - Flaviani, Ester; Supriatna, Eka; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe formulation of the problem in this study are: Does the jump rope game affect the results of high jump learning at SMPN 16 Pontianak? This study aims to determine the effect of traditional jump rope games on high jump learning outcomes. The purpose of this research is to see the effect of learning outcomes before and after treatment. The treatment provided is in the form of a traditional jump rope game on high jump subject matter. The method used in this study is an experimental method with purposive sampling technique. The subjects in this study were students of class VIII D with a sample of 33 people.Data analysis techniques used in this study used the normality test, the homogeneity test and the influence test or (t-test).The results of research and analysis of data that have been done show that there is an influence on traditional jump rope games on high jump learning outcomes. The influence of the results of this study is shown by the ttest value of 30.315> ttable 2.036. The average high jump learning outcomes in the pretest was 11.58 and the posttest was 16.15 and the increase in influence was 39.52%. It can be said that Ho was rejected and Ha was accepted and there was a significant influence.Keywords: Jump Rope, Traditional, High Jump.AbstractThe formulation of the problem in this study are: Does the jump rope game affect the results of high jump learning at SMPN 16 Pontianak? This study aims to determine the effect of traditional jump rope games on high jump learning outcomes. The purpose of this research is to see the effect of learning outcomes before and after treatment. The treatment provided is in the form of a traditional jump rope game on high jump subject matter. The method used in this study is an experimental method with purposive sampling technique. The subjects in this study were students of class VIII D with a sample of 33 people.Data analysis techniques used in this study used the normality test, the homogeneity test and the influence test or (t-test).The results of research and analysis of data that have been done show that there is an influence on traditional jump rope games on high jump learning outcomes. The influence of the results of this study is shown by the ttest value of 30.315> ttable 2.036. The average high jump learning outcomes in the pretest was 11.58 and the posttest was 16.15 and the increase in influence was 39.52%. It can be said that Ho was rejected and Ha was accepted and there was a significant influence.Keywords: Jump Rope, Traditional, High Jump